2019
DOI: 10.26524/ijpefs1936
|View full text |Cite
|
Sign up to set email alerts
|

Competencies and training needs and its impact on determining the professional skills of Algerian elite coaches

Abstract: The main purpose of this study is to develop an understanding of the trainers' perceptions of competency and training needs related to professional skills in accordance with professional experience and academic education. The sample included 76 judo trainers who answered a questionnaire that included a measure that focused on the perceptions of competency and another on training needs. An exploratory factor analysis was used with the maximum probability factor (Oblimin) to determine emerging factors. A compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(47 reference statements)
1
6
0
Order By: Relevance
“…The above is confirmed by the data of (Adel et al, 2019;Mokhtar et al, 2019;Saddek et al, 2020), according to which it was found that during physical exertion, muscle hypertrophy occurs as a result of adaptive-trophic influence (Mukund & Subramaniam, 2020;Teplov, 1982), which is characterized by an increase in thickness and denser packaging of contractile elements of muscle fiber (Haun et al, 2019;Narici et al, 1996). Thus, studies (Annesi, Westcott, Faigenbaum, & Unruh, 2005;Belkadi et al, 2019;Krivoruchko et al, 2018;I. P. Masliak & Mameshina, 2018) indicate that the introduction of functional exercises in the main part of the lesson contributed to a significant improvement in strength abilities of high school students.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The above is confirmed by the data of (Adel et al, 2019;Mokhtar et al, 2019;Saddek et al, 2020), according to which it was found that during physical exertion, muscle hypertrophy occurs as a result of adaptive-trophic influence (Mukund & Subramaniam, 2020;Teplov, 1982), which is characterized by an increase in thickness and denser packaging of contractile elements of muscle fiber (Haun et al, 2019;Narici et al, 1996). Thus, studies (Annesi, Westcott, Faigenbaum, & Unruh, 2005;Belkadi et al, 2019;Krivoruchko et al, 2018;I. P. Masliak & Mameshina, 2018) indicate that the introduction of functional exercises in the main part of the lesson contributed to a significant improvement in strength abilities of high school students.…”
Section: Discussionmentioning
confidence: 65%
“…The research was conducted in accordance with the initiative of the research work "Improvement the process of physical education in educational institutions of various profiles "for 2020-2022 (state registration number IEPS2020/0036) (Belkadi, Benchehida, Benbernou, & Sebbane, 2019) and in accordance with the Helsinki Declaration (World Medical Association, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The integrated analysis of Stricker (2020) shows that resistance training for children and adolescents is beneficial in various aspects, including: muscle strength and explosive power, injury prevention and injury recovery, cardiopulmonary fitness, body composition, bone density (Stricker et al, 2020). Among them, by designing appropriate short-term resistance training, children and adolescents can increase their muscle strength by 30% (Behm, Faigenbaum, Falk, & Klentrou, 2008;Belkadi, Benchehida, Benbernou, & Sebbane, 2019). The integrated analysis of Cavar (2019) unifies the young athletes to conduct resistance training for at least 6 weeks (Cavar et al, 2019) with an average of 2.6 ± 0.9 times per week, the range of training intensity and training volume There are multiple groups (60-80% 1-RM × 2-3 groups × 8-15 reps) from medium load to near maximum load, which can significantly improve muscle strength.…”
Section: Introductionmentioning
confidence: 99%
“…Fitness tests can be very effective for a number of reasons (Hoff 2005) including assessing an athlete's current level of fitness including the identification of an athlete's individual physical (Belkadi et al 2019) (Mohamed et al 2019). The battery presented was adopted for a U13 years men's soccer from 14 teams.…”
Section: Introductionmentioning
confidence: 99%